Can AI Improve Recovery Times After Surgery? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2021)
Artificial intelligence (AI) is no longer a futuristic concept in medicine; it is a present-day reality that is actively reshaping patient care. From diagnos...
Keywords: AI in Surgery and Robotics; Improve; Recovery; Times; Artificial Intelligence; Machine Learning; Healthcare